Effects of different types of meals on postprandial glycaemia in healthy subjects - Agnieszka Lejk; Karolina Myśliwiec; Przemysława Jarosz-Chobot (Pediatric Endocrinology, Diabetes and Metabolism)
Nowadays, continuous glycaemic monitoring systems are used primarily for diabetic patients. The most popular continuous glycaemic monitoring (CGMs) measure the glucose concentration in the interstitial fluid every 1 or 5 minutes, providing the patient with 288 or 1,440 measurements in a day. CGM is also useful for observing sudden changes in glycaemia after the introduction of dietary interventions and those related to physical activity. Peri-prandial glycaemia is defined as the change in blood glucose levels depending on the carbohydrate-containing meal consumed. A state of peri-prandial hyperglycaemia begins when blood glucose levels rise above the level of 140 mg/dl (7.8 mmol/l) within 1–2 hours after food intake in healthy people without diabetes. The influence of the peri-prandial glycaemic response is briefly related to the amount and type of food consumed. Optimising the glycaemic profile is important for our health. The purpose of this article is to summarise the current knowledge of the effects of various meals on peri-prandial glycaemia in healthy individuals.